1992
DOI: 10.1177/002221949202500607
|View full text |Cite
|
Sign up to set email alerts
|

The MMPI-2 Profile of Adults with Learning Disabilities in University and Rehabilitation Settings

Abstract: The primary purpose of this study was to compare the personality profiles of adults with learning disabilities attending a large state university (8 females, 8 males) to those participating in training programs in a rehabilitation setting (8 females, 18 males), in an attempt to identify affective variables that should be considered in transitional and postsecondary program planning. A secondary purpose of the study was to compare the performance of two groups of adults with learning disabilities (i.e., univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 26 publications
6
28
0
Order By: Relevance
“…They seem to be more predisposed to stress and to be at higher risk for developing continuous stress (Cosden & McNamara, 1997), and often exhibit a number of psychological difficulties, including stress and anxiety (Barton & Fuhrman, 1994). These results are consistent with earlier research on college students (Gregg, Hoy, King, Moreland, & Jagota, 1992), in which students with LD from various universities were assessed on academic characteristics. Moreover, students with LD reported lower stress management and lower adaptability (Reiff, Hatzes, Bramel, & Gibbon, 2001), consistently described higher levels of anxiety and persistent feelings of lower self-efficacy, and experienced large gaps between their self-perceived competence and their actual achievements.…”
Section: Stress Perceptionsupporting
confidence: 92%
See 1 more Smart Citation
“…They seem to be more predisposed to stress and to be at higher risk for developing continuous stress (Cosden & McNamara, 1997), and often exhibit a number of psychological difficulties, including stress and anxiety (Barton & Fuhrman, 1994). These results are consistent with earlier research on college students (Gregg, Hoy, King, Moreland, & Jagota, 1992), in which students with LD from various universities were assessed on academic characteristics. Moreover, students with LD reported lower stress management and lower adaptability (Reiff, Hatzes, Bramel, & Gibbon, 2001), consistently described higher levels of anxiety and persistent feelings of lower self-efficacy, and experienced large gaps between their self-perceived competence and their actual achievements.…”
Section: Stress Perceptionsupporting
confidence: 92%
“…Although the findings cannot be compared with those for students with LD in traditional university settings, it appears from previous studies that individuals with LD are more predisposed to stress than their adult counterparts (Barton & Fuhrman, 1994;Gregg, Hoy, King, Moreland, & Jagota, 1992). In addition, the experience of stress was previously reported by college students with LD (Reiff et al, 2001) and supported the assumption that college students with LD may experience increased levels of stress due to academic demands, the study methods, and the intensive need for time management that might exacerbate their preexisting stress.…”
Section: Attribution Of Academic Successmentioning
confidence: 88%
“…In summary, current research suggests that adolescents with LD experience higher levels of trait anxiety than their normally achieving peers (Dollinger et al, 1988;Epstein et al, 1985;Epstein et al, 1986;Gregg et al, 1992;Margalit & Raviv, 1984;Margalit & Shulman, 1986;Margalit & Zak, 1984;Paget & Reynolds, 1984;Ritter, 1989). In addition, adolescents with LD were found to have a significantly higher prevalence of minor somatic complaints.…”
Section: Anxietymentioning
confidence: 78%
“…For example, in the study by Gregg et al (1992), reviewed above, results revealed that the 24 adolescent students with learning disabilities who were being served in a rehabilitation setting demonstrated more depression than would normally be expected in comparison to the norm group. The 26 students receiving rehabilitative services demonstrated a T score of 63.03 on depression, which is more than 1 standard deviation above the expected mean.…”
Section: Depressionmentioning
confidence: 98%
See 1 more Smart Citation